Geographic Mapping of Gender Disparities in Authorship of Cardiovascular Literature - Goel, Ridhima; Sartori, Samantha; Vogel, Birgit; Okoli, Kimberly; Franklin-Bedel, Kayla; Ortega, Rebecca; Wang, Dee Dee; Douglas, Pamela S.; Wang, Tracy Y.; Mehran, Roxana (Journal of the American College of Cardiology, 2024)
Women in cardiology experience considerable gender disparities in publications, which hinders their career advancements to higher faculty and senior leadership positions. However, the extent of these disparities across different types of cardiovascular literature is not well understood. We investigated gender differences in authorship across various cardiovascular publications over a decade and examined geographic variations in the representation of women authors. All papers published from January 1, 2010, to December 31, 2019, in 4 major cardiovascular journals (Journal of the American College of Cardiology, European Heart Journal, Journal of the American Medical Association Cardiology, and Nature Reviews Cardiology) were reviewed. Of the 18,535 papers with 111,562 authors, 20.6% of the authors were women, and 47.7% of the papers had no women authors. Over 10 years, the proportion of women authors remained low (20.7% in 2010 to 21.4% in 2019), with the lowest proportion in editorial papers (14.8%) and the highest in research papers (21.8%). More women as first (34.6%) and last (47.6%) authors were affiliated with institutions in the United States compared with other countries. The proportion of women middle-order authors was higher on papers with women as first authors (29.4% vs 20.5%) or last authors (30.6% vs 21.3%), compared with papers with men as first or last authors, respectively. Over the past decade, the proportion of women authors across all article types in major cardiovascular journals remained low. A call to action is needed to promote women in cardiology and provide them with equitable opportunities. [Display omitted]